2009
DOI: 10.15232/s1080-7446(15)30742-7
|View full text |Cite
|
Sign up to set email alerts
|

CASE STUDY: Effect of Supplemental β-Carotene on Yield of Milk and Milk Components and on Reproduction of Dairy Cows

Abstract: A well-managed, high-producing commercial dairy herd was used to test the impact of supplementing β-carotene (425 mg/d per cow) to lactating multiparous Holstein cows with normally low serum β-carotene (<3 µg/mL). Milk production was not affected by treatment (43.83 and 43.65 kg/d for the β-carotene and control diets). There was no difference because of treatment in overall 3.5% FCM (43.23 vs. 42.24 kg/d for the β-carotene and control diets) but early-lactation cows (0 to 100 DIM) and mature cows (3+ lactation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 21 publications
(22 reference statements)
3
19
0
Order By: Relevance
“…Positive responses in dairy cow fertility and lactation performance have been observed when β-carotene was supplemented after calving (Aréchiga et al, 1998;De Ondarza et al, 2009), although absent (Bindas et al, 1984;Akordor et al, 1986) or negative (Folman et al, 1987) effects on reproduction have been reported. Kaewlamun et al (2011) and Wang et al (2013) have reported benefits in uterine health of cows supplemented with β-carotene before calving.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive responses in dairy cow fertility and lactation performance have been observed when β-carotene was supplemented after calving (Aréchiga et al, 1998;De Ondarza et al, 2009), although absent (Bindas et al, 1984;Akordor et al, 1986) or negative (Folman et al, 1987) effects on reproduction have been reported. Kaewlamun et al (2011) and Wang et al (2013) have reported benefits in uterine health of cows supplemented with β-carotene before calving.…”
Section: Introductionmentioning
confidence: 99%
“…The supplementation of β-carotene postpartum may be required to elicit an increase in plasma levels in early lactation, possibly inducing a positive response in reproductive performance. The β-carotene has improved the pregnancy rate of dairy cows when it was supplemented for at least 90 d (Aréchiga et al, 1998) or 105 d (De Ondarza et al, 2009) postpartum. Although no effect was detectable of the prepartum supplementation of β-carotene on conception rate, cows that conceived at first service and were pregnant at 90 and 150 DIM had higher blood β-carotene concentration postpartum than nonpregnant cows.…”
mentioning
confidence: 99%
“…of milk yield during the experimental periodAs with canola seed diet, no significant differences (P>0.10) were reported either for milk yield with the marjoram diet. Those results were in agreement with other studies in which milk yield was not affected by the inclusion of an antioxidant in the diet; Vitamin E(Smith et al, 2003), 0,025% DM Agrado Plus (He and Armentano, 2010) and βcarotene(De Ondarza et al, 2009). However others studies reported a significant improvement of the milk yield(Vázquez-Añón et al, 2008;Wang et al, 2010;Wang et al, 2012) Wang et al, (2012).…”
supporting
confidence: 91%
“…The positive effects in cows or pigs reported in the literature include decreased service per conception, increased number of viable embryos/reduced embryonic mortality, improved embryo quality, improved immunity with reduced incidence of retained placenta and metritis, increased pregnancy rate, increased percentage of milk fat (with unaffected milk yield), improved protection of the mammary gland against infection as a result of increased intracellular killing of microbes by phagocytes, and higher plasma progesterone and oestradiol levels in the cat (Brief and Chew, 1985;Iwańska et al, 1985;Daniel et al, 1991a;Coffey and Britt, 1993;Preś et al, 1993;Chew et al, 2001;Schweigert et al, 2002;Sales et al, 2008;Spears and Weiss 2008;de Ondarza et al, 2009). Experimental evidence suggests that beta-carotene can serve as an alternative vitamin A source for the in situ synthesis of retinoids in the mammalian embryo (Kim et al, 2011).…”
Section: Reproduction and Immunologymentioning
confidence: 99%